The Improving the Skills and Creativity of Female Students through Extracurricular Activities at Darul Ulum Boarding School - Elsya Febriani; Husni Darmawan; Muhammad Ridwan Sururi; Pita Andri Yani; Reni Tri Lestari; Erlin Wulandari; Findi Mareta Biliovita; Tias Asih Triyanti; Syaivudin Al-Jazuli; Sunnilam Fatimah (CV. Creative Tugu Pena, 2022)
This research is a qualitative field study conducted at Pondok Pesantren Darul Ulum Seputih Banyak, Central Lampung. Data were collected through interviews, observation, and documentation, with data validity ensured using source and technique triangulation. Data analysis involved data collection, reduction, presentation, and conclusion drawing. The programs implemented have enabled female students (santri putri) to enhance their potential and realize their talents, particularly through extracurricular activities in the arts. These programs have fostered skill development and creativity among the students. Moreover, the increasing number of programs has boosted student enthusiasm, facilitating better absorption of the educational material provided. The success of enhancing the students' skills and creativity through artistic extracurricular activities is inseparable from the commitment of the administrators in continuously improving these programs. Their dedication has earned positive responses from the students and has become a strong motivational factor, which, in turn, contributes to increased learning enthusiasm. This enthusiasm enhances the students’ ability to grasp lessons quickly, ultimately shaping female students who are both skilled and creative .Keywords : Extracurricular Activities, Students' Skills and Creativity